Health inequalities: Embodied evidence across biological layers - Vineis, Paolo; Delpierre, Cyrille; Castagné, Raphaële; Fiorito, Giovanni; McCrory, Cathal; Kivimaki, Mika; Stringhini, Silvia; Carmeli, Cristian; Kelly-Irving, Michelle (Social science & medicine, 2020)
Socioeconomic disparities have been documented in major non-communicable diseases and in their risk factors, such as obesity, hypertension, diabetes, smoking, physical inactivity, unhealthful diet and heavy drinking. However, a key research question has remained unanswered: is there a separate biological embodiment of socio-economic conditions underlying health disparities, additional and independent of those risk factors? As lifelong socioeconomic circumstances cannot be randomised, one way forward is the examination of different biological layers of evidence, including molecular changes. In this methodological paper we report the association of socio-economic disadvantage with (a) long-term health outcomes, before and after taking risk factors into account; (b) biological intermediaries that increase susceptibility to disease, such as childhood obesity; (c) intermediate circulating biomarkers and omic measurements (transcriptomics, DNA methylation, inflammatory proteins, allostatic load); and (d) immunity. In our Lifepath consortium, these analyses have been performed in several cohort studies, countries and contexts, and at different stages of the life course in up to 1.7 million subjects. The main goal is to test the assumption that each layer (death, functional outcomes, DNA, RNA, proteins, infections) is characterized by different types of bias and confounding, and that consistency across layers reinforces causality assessment. The findings show consistent associations of social disparities with unfavourable health outcomes spanning inflammatory biomarkers, DNA or RNA-based markers, infection, indicators of physical functioning and mortality. Although each of these associations has a different set of confounders, a dose-response relationship is nevertheless consistently observed, thus showing the power of our multi-layered approach. This new evidence supports biological embodiment of social disadvantage, in addition to the impact of known (mainly behavioural) risk factors for disease. •Is there a biological embodiment of socio-economic conditions?•We have analysed multiple health indicators spanning mortality via omic measurements.•We show steady associations of social disparities with all the biological outcomes.•Associations were robust to adjustment for confounders.•Dose-response relationships were detected.